Iron Chemistry of Hemilabile SNS Ligands: Synthesis, Reactivity, and Catalytic Applications - Das, Uttam (Université d'Ottawa / University of Ottawa, 2018)
The development of abundant and economical first-row transition metal-based catalysts is an appealing area of research for efficient and selective chemical transformations. In this context, iron complexes are highly desirable as they feature a range of accessible oxidation states allowing for transfer of one or two electrons to or from a substrate. Therefore, over the past two decades, many iron-based catalysts have been developed, extensively studied, and exploited for catalysis ranging from oxidation and reduction to C-C bond forming reactions. In homogeneous transition metal catalysis, the ligand plays a vital role in determining activity and selectivity of the above stated catalytic reactions. Some key features of ligands that support both stoichiometric and catalytic reactions of metal complexes include: 1) strong chelation ability to metals, 2) tunability of donor atoms, 3) strong field ligands such as phosphine, phosphite, CO, and hydride favoring low-spin complexes, 4) hemilability allowing substrate activation via reversible dissociation of one donor atom, and 5) redox-activity enabling donation or accepting of electrons, thus avoiding a change of metal oxidation state. To this end, bifunctional ligands containing the above described properties have emerged as important elements in chemical synthesis and in catalysis. Iron and other transition metal complexes containing multidentate bifunctional ligands have recently been shown to activate small molecules and catalyze a number of chemical transformations with activity and selectivity typical of more well-studied precious metals. The objective of this thesis is to further advance the field of bifunctional ligands by preparing new sterically svelte tridentate ligands with a mixture of hard nitrogen and soft sulfur donors and to investigate their iron chemistry. The overall goal is to then explore the utility of these iron complexes as potential bifunctional catalysts. Chapter 2 describes a one-step synthesis of a new SMeNHS ligand in excellent yield that undergoes ring-opening on treatment with Fe(OTf)2 affording a thiolate-bridged, trinuclear iron complex, [Fe3(µ2-SMeNS−)4](OTf)2. The structure, spectroscopic, magnetic, and computational studies of this iron complex are provided along with its solvent-dependent reactivity towards monodentate donor ligands that yields both dinuclear and mononuclear derivatives. Chapter 3 describes the formation of an electron-rich Fe(II) thiolate complex, [Fe(SMeNS)(PMe3)3](OTf) and its substitution reactivity with both mono- and bidentate donor ligands. On heating this complex, an oxidative thioether Caryl-S bond cleavage is observed, leading to a cationic Fe(III)-CNS thiolate analog. Reduction of this Fe(III) species with cobaltocene yielded a neutral Fe(II)-CNS thiolate complex. To investigate the bifunctional activity of these Fe(II) complexes, both Fe(II)-SNS and -CNS species were assessed as precatalysts for amine-borane dehydrogenation. Chapter 4 employs the SMeNHS ligand in formation of a neutral, imine-coupled Fe-N2S2 complex that serves as an efficient and selective aldehyde hydroboration catalyst using pinacolborane. A reaction profile kinetic analysis implicates the hemilability and redox-active properties of this complex. Chapter 5 introduces the new unsymmetrical amine ligand, SMeNHSMe, and details its iron chemistry with formation of a pseudooctahedral Fe(II) bis(amido) complex. The Mössbauer spectra, MCD study, and DFT calculations support formation of a minor five-coordinate isomer in solution due to the hemilability of the six-membered ring thioether group. Reactivity studies of this Fe(II) species with a variety of donor ligands confirmed this lability and protonation at nitrogen yielded a cationic Fe(II) amine-amido complex. Reaction of the latter with the tridentate phosphine, triphos, gave a 16e-, low-spin, square-pyramidal Fe(II) complex that proved to be a robust precatalyst that is more active for dehydrogenation of dimethylamine-borane vs. ammonia-borane. Formation of a monohydride catalyst resting state under these reaction conditions is suggestive of a bifunctional activation pathway. Finally, Chapter 6 concludes the outcomes of the iron chemistry of hemilabile SNS ligands and discusses future directions and opportunities to extend these ligand systems to other transition metals. The knowledge gained by the stoichiometric and catalytic reactivity of iron-SNS complexes presented herein contributes to our understanding of bifunctional catalysis. With the increasing demand for base metal catalysts in chemical industry for efficient and selective synthesis of value-added chemicals, iron SNS complexes could offer economical, active, and selective catalyst precursors.
Keywords: hemilabile; iron; SNS ligands; catalysis